2021
DOI: 10.3390/geosciences11080349
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Enhanced Geothermal System Development Scenarios for District Heating and Cooling of the Göttingen University Campus

Abstract: The huge energy potential of Enhanced Geothermal Systems (EGS) makes them perspective sources of non-intermittent renewable energy for the future. This paper focuses on potential scenarios of EGS development in a locally and in regard to geothermal exploration, poorly known geological setting—the Variscan fold-and-thrust belt —for district heating and cooling of the Göttingen University campus. On average, the considered single EGS doublet might cover about 20% of the heat demand and 6% of the cooling demand o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…EGS is also a promising source of energy. However, electricity and thermal power generation is threatened by technical issues [18], and a proper economic evaluation of different scenarios is crucial for further implementation of these solution at larger scale [19,20].…”
Section: Technical Economic and Environmental Assessment For Oil To G...mentioning
confidence: 99%
See 2 more Smart Citations
“…EGS is also a promising source of energy. However, electricity and thermal power generation is threatened by technical issues [18], and a proper economic evaluation of different scenarios is crucial for further implementation of these solution at larger scale [19,20].…”
Section: Technical Economic and Environmental Assessment For Oil To G...mentioning
confidence: 99%
“…Romanov and Leiss [19] focused their study entitled "Analysis of Enhanced Geothermal System Development Scenarios for District Heating and Cooling of the Göttingen University Campus" on potential scenarios of EGS development in the poorly known Variscan basement below Göttingen, for district heating and cooling of the University campus. On average, they demonstrated that a single EGS doublet could cover about 20% of the heat demand and 6% of the cooling demand of the campus.…”
Section: Technical Economic and Environmental Assessment For Oil To G...mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have been conducted on the energy systems supplying heating and cooling (H and C) in academic buildings or entire campuses. In [20], the potential of Enhanced Geothermal Systems for districts H and C of the Göttingen University campus has been assessed. The EGS heat output should be at least 11 MW.…”
Section: Introductionmentioning
confidence: 99%
“…[37]. Romanov and Leiss [38] further analysed the case study on enhanced geothermal systems for application in Göttingen University. Moreover, Haghiabi et al [39] conducted an interesting study to predict the velocity vector around a cylindrical weir using doublet potential theory.…”
Section: Introductionmentioning
confidence: 99%